Legalitas Investasi Pemerintah Daerah Terhadap Perusahaan Minuman Keras Untuk Menambah APBD: Tinjauan Maqasid Syariah - Ita Wardatul Janah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2021)
Abstract: Local governments have the task of increasing regional cash income, one of which is obtained through dividends from investments. The liquor industry is a business field that is closed to investment activities because it is against the general morality of the Indonesian people, but in fact there are limited companies whose shares are owned by local governments. This study uses a maqa>sid syari>â€™ah approach from Jaseer Auda's perspective. So that it is obtained: first, the local government's policy to invest in the liquor industry with the excuse of adding to the APBD is wrong. Actually, liquor investment does not have urgency to have an economic or social impact, it actually causes underdevelopment of human development and human rights violations. Local governments should have protect the public by making policies so that people do not drink alcohol instead of making them consume alcohol because of the investment in that sector. second, investment in liquor only provides a few benefits, on the contrary the harm (danger) caused is much greater, local governments need to take priority policies to eliminate harm rather than take a benefit. Â Key word: Liquor Investment, Local Government, Maqa>sid Syari>â€™ah",